Influence of process pressure on HW-CVD deposited a-Si : H films - Jadkar, Sandesh R.; Sali, J. V.; Kshirsagar, S. T.; Takwale, M. G. (Solar Energy Materials and Solar Cells, 2005)
Hydrogenated amorphous silicon (a-Si:H) films were deposited using pure silane (SiH4) without hydrogen dilution by hot wire chemical vapor deposition (HW-CVD) technique. The electrical, optical, and structural properties of these films are systematically studied as a function of process pressure (P-r). The device quality a-Si:H films with a photosensitivity > 10(5) were deposited at a deposition rate >40 Angstrom/s at low process pressure. However, a-Si:H films deposited at higher process pressures show degradation in their electrical and structural properties. The FTIR spectroscopic analysis showed that a-Si:H films deposited at low process pressure contain hydrogen mainly in mono-hydrogen (Si-H) configuration whereas films deposited at higher process pressure have hydrogen in di-hydrogen (Si-H-2) or poly hydrogen (SiH2)(n) complexes. The hydrogen content (C-H) in the films was found to be less than 4 at.% over the entire range of process pressure studied. This indicates that the growth of a-Si:H films is mainly from the atomic species (Si and H) evaporated from the hot filament and hydrogen gets incorporated in the film via gas-phase reactions and substrate gas interactions. The band gap, however was found similar to1.71 eV or much higher. We attribute high band gap at low hydrogen content may be due to presence of microvoids. Raman spectroscopic analysis showed increase in structural disorder and Rayleigh scattering with increase in the process pressure. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrical properties; FTIR spectroscopy; hot wire chemical vapor deposition; hydrogenated amorphous silicon; Raman spectroscopy

Observation of photoconductivity in Sn-doped ZnO nanowires and their photoenhanced field emission behavior - Sheini, Farid Jamali; More, Mahendra A.; Jadkar, Sandesh R.; Patil, K. R.; Pillai, Vijaymohanan K.; Joag, Dilip S. (Journal of Physical Chemistry C, 2010)
Sn-doped ZnO nanowire films have been Successfully synthesized by electrodeposition oil zinc foil followed by annealing in air at 400 degrees C for 4 h. The XRD patterns of the annealed specimens exhibit I set of well-defined diffraction peaks indexed to the wurtzite phase of ZnO. The Surface morphology of the as-synthesized films showed a network of densely packed flakes/sheets oil the Substrate. However, upon annealing, the formation of ZnO nanowires, processing length in the range of several micrometers and diameter less than 150 nm, oil the entire substrate is observed. The relative atomic percentage of Sri, estimated from the energy dispersive spectra, was found to be 0.5 and 2.0 in the ZnO films deposited for 10 and 40 min durations, respectively. Front the field emission studies, the Values of the turn-on field and threshold field, required to draw emission Current density of 10 and 100 mu A/cm(2), are observed to be 0.68 and 1.1 V/mu m for 0.5% Sn-doped ZnO and 1.72 and 2.25 V/mu m for 2.0% Sn-doped ZnO, respectively. The field emission Current stability investigated for a duration Of h at the preset value of 100 mu A is found to be excellent. A prominent photoenhancement in the field emission Current upon visible light illumination of the Sn-doped ZnO nanowires films has been observed. This enhancement has been attributed to the photoconductivity of the Sn-doped ZnO.

Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets

Effect of plasma treatment on multilayer graphene: X-ray photoelectron spectroscopy, surface morphology investigations and work function measurements - Patil, Urmila V.; Pawbake, Amit S.; Machuno, Luis G. B.; Gelamo, Rogerio V.; Jadkar, Sandesh R.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report here the effect of plasma treatment on multilayer graphene samples as determined by X-ray photoelectron spectroscopy and surface morphology studies with atomic force microscopy, scanning electron microscopy and transmission electron microscopy. The plasma treatment was modified to introduce controlled levels of defects and functionalities to the graphene samples to give tunable properties. The elemental composition and structure were investigated by XPS and micro Raman spectroscopy. The XPS study showed that there was a slight variation in the sp(2)/sp(3) hybridization ratio between the plasma-treated samples and the pristine sample. Kelvin probe measurements were carried out on all the multilayer graphene samples and indicated a slight variation in the work function of the graphene samples after plasma treatment.

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

High performance humidity sensor and photodetector based on SnSe nanorods - Pawbake, Amit S.; Jadkar, Sandesh R.; Late, Dattatray J. (Materials Research Express, 2016)
Tin selenide (SnSe) nanorods were synthesized using a. one-step solvothermal route and. their. humidity sensing and photodetection performance at room temperature were investigated. The results depict. that SnSe nanorod-based humidity and photosensors have. good long-term stability, are. highly sensitive and have. fast response and recovery times. In the. case of the. humidity sensor it was observed that the resistance of the films decreased. with increasing relative humidity (RH). The humidity sensing behaviors were investigated in the range. 11-97% RHat room temperature. A. response time of similar to 68 s and recovery time of similar to 149 s were observed for. the humidity sensor. The photosensing behavior showed. typical response/recovery times of similar to 3 s with highly reproducible behavior.

Highly transparent wafer-scale synthesis of crystalline WS2 nanoparticle thin film for photodetector and humidity-sensing applications - Pawbake, Amit S.; Waykar, Ravindra G.; Late, Dattatray J.; Jadkar, Sandesh R. (ACS Applied Materials & Interfaces, 2016)
In the present investigation, we report a one-step synthesis method of wafer-scale highly crystalline tungsten disulfide (WS2) nanoparticle thin film by using a modified hot wire chemical vapor deposition (HW-CVD) technique. The average size of WS2 nanoparticle is found to be 25-40 nm over an entire 4 in. wafer of quartz substrate. The low-angle XRD data of WS2 nanoparticle shows the highly crystalline nature of sample along with orientation (002) direction. Furthermore, Raman spectroscopy shows two prominent phonon vibration modes of E12g and A1g at similar to 356 and similar to 420 cm(-1), respectively, indicating high purity of material. The TEM analysis shows good crystalline quality of sample. The synthesized WS2 nanoparticle thin film based device shows good response to humidity and good photosensitivity along with good long-term stability of the device. It was found that the resistance of the films decreases with increasing relative humidity (RH). The maximum humidity sensitivity of 469% along with response time of similar to 12 s and recovery time of similar to 13 s were observed for the WS2 thin film humidity sensor device. In the case of photodetection, the response time of similar to 51 s and recovery time of similar to 88 s were observed with sensitivity similar to 137% under white light illumination. Our results open up several avenues to grow other transition metal dichalcogenide nanoparticle thin film for large-area nanoelectronics as well as industrial applications.
Keywords: chemical vapor deposition; humidity sensor; nanoparticle; photosensor; thin film; tungsten disulfide

Large area chemical vapor deposition of monolayer transition metal dichalcogenides and their temperature dependent Raman spectroscopy studies - Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; Late, Dattatray J. (Nanoscale, 2016)
We investigate the growth mechanism and temperature dependent Raman spectroscopy of chemical vapor deposited large area monolayer of MoS2, MoSe2, WS2 and WSe2 nanosheets up to 70 mu m in lateral size. Further, our temperature dependent Raman spectroscopy investigation shows that softening of Raman modes as temperature increases from 80 K to 593 K is due to the negative temperature coefficient and anharmonicity. The temperature dependent softening modes of chemical vapor deposited mono-layers of all TMDCs were explained on the basis of a double resonance phonon process which is more active in an atomically thin sample. This process can also be fundamentally pertinent in other emerging two-dimensional layered and heterostructured materials.

Temperature dependent raman spectroscopy and sensing behavior of few layer SnSe2nanosheets - Pawbake, Amit S.; Date, Abhijit; Jadkar, Sandesh R.; Late, Dattatray J. (Chemistryselect, 2016)
Two- dimensional (2D) tin diselenide (SnSe2) nanosheets were synthesized using solvothermal route in one step and perform its humidity sensing, photo sensing and temperature dependant Raman spectroscopy studies. The sensor devices based on few layer SnSe2 nanosheets were prepared and which shows fast response as well as recovery time along with good long-term stability and high sensitivity. The photo sensing behavior shows the typical response time and recovery time to be similar to 310 ms and similar to 340 ms respectively for visible light illumination. The room temperature humidity sensing behaviors were studied in the range of 11-97% relative humidity (RH). The ob-served sensitivity of similar to 81% with response time of similar to 74 sec and recovery time of similar to 30 sec were calculated for the few layer SnSe2 nanosheets based humidity sensor. The humidity sensing results confirms the high stability of the device even after six months of time. The temperature dependent Raman spectroscopy investigation in the range of 80 K to 593 K were carried out which shows the negative temperature coefficient and softening of Raman modes as we increases the temperature. The softening modes of SnSe2 nanosheets due to temperature were explained on the basis of a double resonance process which is more active in an atomically thin sample.

Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.

Optical antenna effect on SiNWs/CuS photodiodes - Yenchalwar, Sandeep G.; Rondiya, Sachin R.; Shinde, Pravin N.; Jadkar, Sandesh R.; Shelke, M. V. (Physica Status Solidi A-Applications and Materials Science, 2017)
One-dimensional architectures between silicon nanowires (SiNWs) and CuS were fabricated by radio-frequency (RF) magnetron sputtering and analyzed for solid-state photodetector application. Inspired by the subwavelength optical concentration by the surface plasmons on metal nanostructures at the nanoscale, we investigated the effect of gold nanorods (AuNRs) on the optical absorption and photodetection properties of the heterojunction photodiode. AuNRs acting as an optical trapping antenna enhances the light absorption, consequently boosting the photocurrent from the device. A maximum photoresponsivity of 0.36 mA W-1 was achieved under 665 nm excitation wavelength independent of the bias, a value similar to 13 times higher than for the heterojunction photodiode without AuNRs. Such plasmonic sensitization can be useful for improving the sensitivity of visible as well as IR photodetectors. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim

Synthesis of orthorhombic-molybdenum trioxide (α-MoO3) thin films by hot wire-CVD and investigations of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit S.; Waykar,Ravindra G.; Jadhavar, Ashok Arjun; Mayabadi, Azam; Date, Abhijit; Late, Dattatray J.; Pathan, Habib M.; Gosavi, Suresh W.; Jadkar, Sandesh R. (Journal of Materials Science Materials in Electronics, 2017)
In present work, we report synthesis of orthorhombic-molybdenum trioxide (α-MoO 3) thin films using home-build hot wire-CVD (HW-CVD) method simply by heating the Mo filament in a controlled O 2 atmosphere. The formation of α-MoO 3 was confirmed by low angle-XRD and Raman spectroscopy. Low angle-XRD analysis revealed that α-MoO 3 crystallites have orientations along (110), (101) and (111) directions while Raman spectroscopy analysis shows two prominent vibrational modes ~819 and ~994 cm −1 associated with Mo 2–O and Mo=O respectively. SEM and TEM analysis show the formation of nano-sheets like morphology of α-MoO 3 thin films. The SAED pattern shows highly crystalline nature of α-MoO 3. The humidity-sensing properties were investigated at room temperature by fabricating the two probe device. The humidity sensing results showed n-type behavior of α-MoO 3. The maximum humidity sensitivity of ~6957% along with response time of ~66 s and recovery time of ~5 s were observed for α-MoO 3 thin film humidity sensor device. Our results have opened up a new avenue to grow α-MoO 3 for humidity sensor applications.

Uncovering the origin of enhanced field emission properties of rGO-MnO(2)heterostructures: a synergistic experimental and computational investigation - Rondiya, Sachin R.; Karbhal, Indrapal; Jadhav, Chandradip D.; Nasane, Mamta P.; Davies, Thomas E.; Shelke, V. Manjusha; Jadkar, Sandesh R.; Chavan, Padmakar G.; Dzade, Nelson Y. (RSC Advances, 2020)
The unique structural merits of heterostructured nanomaterials including the electronic interaction, interfacial bonding and synergistic effects make them attractive for fabricating highly efficient optoelectronic devices. Herein, we report the synthesis of MnO(2)nanorods and a rGO/MnO(2)nano-heterostructure using low-cost hydrothermal and modified Hummers' methods, respectively. Detailed characterization and confirmation of the structural and morphological properties are doneviaX-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Compared to the isolated MnO(2)nanorods, the rGO/MnO(2)nano-heterostructure exhibits impressive field emission (FE) performance in terms of the low turn-on field of 1.4 V mu m(-1)for an emission current density of 10 mu A cm(-2)and a high current density of 600 mu A cm(-2)at a relatively very low applied electric field of 3.1 V mu m(-1). The isolated MnO(2)nanorods display a high turn-on field of 7.1 for an emission current density of 10 mu A cm(-2)and a low current density of 221 mu A cm(-2)at an applied field of 8.1 V mu m(-1). Besides the superior FE characteristics of the rGO/MnO(2)nano-heterostructure, the emission current remains quite stable over the continuous 2 h period of measurement. The improvement of the FE characteristics of the rGO/MnO(2)nano-heterostructure can be ascribed to the nanometric features and the lower work function (6.01 and 6.12 eV for the rGO with 8% and 16% oxygen content) compared to the isolated alpha-MnO2(100) surface (phi= 7.22 eV) as predicted from complementary first-principles electronic structure calculations based on density functional theory (DFT) methods. These results suggest that an appropriate coupling of rGO with MnO(2)nanorods would have a synergistic effect of lowering the electronic work function, resulting in a beneficial tuning of the FE characteristics.

Lead-free Cs2AgBiCl6 double perovskite: experimental and theoretical insights into the self-trapping for optoelectronic applications - Rahane, Swati N.; Rahane, Ganesh K.; Mandal, Animesh; Jadhav, Yogesh; Godha, Akshat; Rokade, Avinash; Shah, Shruti; Hase, Yogesh; Waghmare, Ashish; Saykar, Nilesh G.; Roy, Anurag; Salgaonkar, Kranti N.; et al. (ACS Physical Chemistry Au, 2024)
Lead-free double perovskites (DPs) will emerge as viable and environmentally safe substitutes for Pb-halide perovskites, demonstrating stability and nontoxicity if their optoelectronic property is greatly improved. Doping has been experimentally validated as a powerful tool for enhancing optoelectronic properties and concurrently reducing the defect state density in DP materials. Fundamental understanding of the optical properties of DPs, particularly the self-trapped exciton (STEs) dynamics, plays a critical role in a range of optoelectronic applications. Our study investigates how Fe doping influences the structural and optical properties of Cs2AgBiCl6 DPs by understanding their STEs dynamics, which is currently lacking in the literature. A combined experimental–computational approach is employed to investigate the optoelectronic properties of pure and doped Cs2AgBiCl6 (Fe–Cs2AgBiCl6) perovskites. Successful incorporation of Fe3+ ions is confirmed by X-ray diffraction and Raman spectroscopy. Moreover, the Fe–Cs2AgBiCl6 DPs exhibit strong absorption from below 400 nm up to 700 nm, indicating sub-band gap state transitions originating from surface defects. Photoluminescence (PL) analysis demonstrates a significant enhancement in the PL intensity, attributed to an increased radiative recombination rate and higher STE density. The radiative kinetics and average lifetime are investigated by the time-resolved PL (TRPL) method; in addition, temperature-dependent PL measurements provide valuable insights into activation energy and exciton–phonon coupling strength. Our findings will not only deepen our understanding of charge carrier dynamics associated with STEs but also pave the way for the design of some promising perovskite materials for use in optoelectronics and photocatalysis.

PANI-grafted boron, nitrogen co-doped carbon fiber: An outstanding, high-performance supercapacitor electrode - Nayan, Rajiv; Sinha, Shubhra; Dixit, Vaibhav; Satnami, Manmohan L.; Ghosh, Kallol K.; Pervez, Shamsh; Deb, Manas Kanti; Shrivas, Kamlesh; Rai, Manish K.; Yenchalwar, Sandeep G.; Wasnik, Kundan; Jadkar, Sandesh R.; et al. (JOURNAL OF ENERGY STORAGE, 2024)
Keywords: Composite; polyaniline; Solid-state supercapacitor

Field emission performance of 2D Ti2CT x (T x = O2, F2, O-F) MXene: experimental insights and theoretical endorsement - Kakade, Prashant M.; Aher, Rahul; Kachere, Avinash R.; Cho, Jinill; Deore, Amol; Jadkar, Sandesh R.; Chauhan, Inderjeet; Kim, Taesung; Mandlik, Nandkumar T.; Kim, Ji Man; Bulakhe, Ravindra N. (ACS Applied Nano Materials, 2026)
Field emission (FE) is an important electron emission mechanism for vacuum microelectronic devices; however, conventional emitters often exhibit high turn-on fields, limited emission stability, and degradation during prolonged operation. Two-dimensional MXenes have recently emerged as promising FE materials due to their remarkable electrical conductivity, comparatively low work function, and tunnelable surface terminations. Nevertheless, most studies have focused on Ti3C2T x MXene, while other compositions such as Ti2CT x remain largely unexplored, particularly regarding the influence of surface terminal groups on their electronic and emission properties. Herein, Ti2CT x (T x = -F2, -O2, -OF) MXene was synthesized via selective chemical etching of the Ti2AlC MAX phase and investigated for its FE characteristics. The material exhibits a polycrystalline hexagonal layered structure with a high specific surface area of 349.02 m2 g-1. Ti2CT x MXene demonstrates excellent FE performance with a low turn-on field of 1.56 V mu m-1 and a threshold field of 2.0 V mu m-1 (at 10 mu A cm-2), along with a stable emission for 4 h. Density functional theory calculations further reveal that surface terminations strongly influence the electronic structure and work function, with the experimental value of 4.66 eV closely matching the -F2 termination. These results highlight Ti2CT x MXene as a promising material for stable and efficient FE applications.
Keywords: 2D Ti2CT x MXene; field emission; TDOS and PDOS; Turn-on voltage; Work function